Effects of Traditional Team Games on Child Emotional Isolation Symptoms in Orphanages - Irma Zulfahuri Aini; Agus Mahendra; Ricky Wibowo (TEGAR: Journal of Teaching Physical Education in Elementary School, 2022)
An orphanage is an unfamiliar place for the children who live in it. Playing activities could give the children the opportunity to express all their emotions naturally. The purpose of this study was to determine the effect of traditional games on the personality, depression, social worthiness, and emotional isolation of children in an orphanage. The population of the study were 13 elementary school-age children in an orphanage in Bandung. Sampling technique used total sampling technique with inclusion and exclusion criteria. The sample of this study included 10 boys. The instrument used was the emotional isolation symptom test with UCLA Loneliness Version 3. This study used One Group Pre-test Post-test design. Analysis of research data employed quantitative descriptive analysis technique. The results showed that the traditional games, named Bentengan and Boy-boyan, had a significant effect on emotional isolation, but did not have a significant effect on child personality, social worthiness, and depression. Children who often play had a decreased level of emotional isolation symptoms because playing was carried out together creating an emotional bond in friendship so that the child felt accepted and did not feel lonely.